COMPARISON ANALYSIS OF MALE AND FEMALE BUYING DECISION TOWARDS SOFTWARE PIRACY PRODUCT - Kumendong, Gloria Estevanie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Consumer buying decision is indeed a unique and interesting discussion, because this is related to variuos factors in the various dimensions of differential human life. One interesting facts which became attention of many people is the circulation phenomenon of piracy as a new alternative in the consumption choices of consumers. This research is conduct in Manado. The objectives of this research are to analyze the significant difference between male and female consumer buying decision and consumer purchase intention, partially and simultaneously. This research is a comparison type. This reasearch is a quantitative method since using questionnaire as a tool to gather data and analysis. Using the t-test model to answer the research problem. The hypothesis of this research is to conduct a conclusion of there is a significant difference of male and female buying decision and puchase intention. The population observed are the IBA Students of Faculty of Economy and Business UNSRAT with sample as many as 50 male respondents. This study reveals that consumer buying decision of male and female have no significant difference which means both of male and female students have the same thought while making a decision of buying pirated software, so any manufacturer or individual need to evaluate standard that use in creating the piracy software. Keywords: consumer buying decision, consumer purchase intention.